Comparative Study of Back-propagation and PSO Based Back-propagation for Anemia Diagnosis in Pregnant Ladies - Sharma, Neha; Khullar, Vikas; Luhach, Ashish (International Journal of Science, Engineering and Computer Technology, 2017)
A major problem in medical science is attaining the correct diagnosis of anemia for precedence of its treatment. According to WHO survey anemia is one of the most commonly encountered medical deficiency during pregnancy WHO (2001). Here Artificial Neural Network (ANN) based diagnosis model is propose to determine the prospect for the anemia in pregnant will trained by using Back propagation (BP) algorithm and particle swann optimization (PSO). Algorithms will simulate using Python and their performance has been evaluated using accuracy factor. The perfonnance comparison helps to detennine the best model for diagnosis of anemia in pregnant ladies. Al-Shayea (2011); Gandomi, Yang, and Talatahari (2012); Mohaghegi, Del Valle, Venayagamoorthy, and Harley (2005).